Fear of Re-Injury Post-ACL Reconstruction: Cognitive-Behavioral Interventions - Al-Mhanna, Sameer Badri; Tanveer, Moazzam (Health Nexus, 2025)
This study evaluated the efficacy of cognitive-behavioral interventions, particularly graded exposure therapy, in addressing fear of re-injury among athletes following anterior cruciate ligament (ACL) reconstruction, comparing outcomes with traditional cognitive restructuring and standard rehabilitation approaches. A randomized controlled trial was conducted with 120 athletes (ages 16-25) at 3-6 months post-ACL reconstruction, randomly assigned to graded exposure (GE), cognitive restructuring (CR), or standard care (SC) groups. The GE protocol incorporated systematic desensitization through sport-specific movements, while CR focused on modifying maladaptive beliefs about re-injury. Primary outcomes included changes in Tampa Scale for Kinesiophobia (TSK-11) scores, biomechanical assessments during drop-jump tasks, and return-to-sport rates, measured at baseline, 6, 12, and 24 weeks. The GE group demonstrated superior outcomes, with a 35.3% reduction in fear scores (TSK-11) compared to 33.1% in CR and 22.7% in SC (p < 0.001). Biomechanical improvements, including knee flexion angle and limb symmetry, were significantly greater in GE (p < 0.001). Qualitative findings highlighted enhanced movement confidence and reduced somatic fear in GE participants. Return-to-sport rates were highest in GE (68.9%) versus CR (62.5%) and SC (45.0%) (p = 0.007). Graded exposure therapy emerges as the most effective intervention for reducing fear of re-injury post-ACLR, combining psychological and neuromuscular benefits. These findings support integrating exposure-based protocols into standard rehabilitation programs during early-to-mid recovery phases to optimize both physical and psychological readiness for return to sport.